"It's not often we get a visit from a beautiful woman!" The body in client-auditor interactions and the masculinity of accountancy. (October 2019) - Bitbol-Saba, Nathalie; Dambrin, Claire
Abstract: Research on gender and auditing tends to focus on firms' internal environment. This study looks instead at how the bodies of female auditors are brought into play in situations involving interactions with clients. We build on Goffman's work on gender and interaction order to gain a better understanding of the gendered dynamics which underpin interactions between auditors and their clients and connect with power asymmetries. Drawing on observations of client-auditor interactions and semi-structured interviews, we reveal three gendered dynamics contributing to the masculinity of accountancy. (1) We highlight the hierarchy formation process between male and female auditors when interacting with clients. (2) We show how female bodies are used by female auditors and instrumentalized by their organizations to satisfy the supposed expectations of clients. (3) We show how female auditors are set up as sexual objects in their interactions with clients.